Manuk Abeghian’s Linguistic Conception as a Guarantee of the Renewal of Modern Armenian Studies - Gyulzatyan, Davit (Bulletin of Yerevan University B: Philology, 2026)
Manuk Abeghyan was the first to formulate a scientific theory of Eastern Armenian, basing it on the actual structure of our language.Due to the turmoil of the time, individuals educated in the West were pushed into the background, and as a consequence, the valuable scholarly work they had produced was likewise marginalized. Undoubtedly, in the post-Abeghyan period there were valuable and noteworthy studies devoted to Modern Armenian; however, it must be noted that this period is largely characterized as a Russified school of Armenian linguistics. This is because subsequent linguists abandoned M. Abeghyan’s syntax—so closely aligned with the nature of our language and still competitive today, in its logic and fundamentality, with Western schools—and instead modeled the grammar of Eastern Armenian largely on Russian grammar.There is a need to reconsider numerous phonetical and morphological issues that, for various reasons, received distorted assessments in the post-Abeghyan period.This does not mean that questioning or critiquing the views of the scholar M. Abeghyan is impermissible. By no means. Rather, the value that Abeghyan introduced into Armenian linguistics must be duly acknowledged by restoring those principles derived from the essence of our language that the scholar himself revealed.Abeghyan’s theory is interesting and important in terms of its potential. It is a conceptual framework that enables creative work, and the present study represents such an attempt—to reaffirm several essential principles of the Abeghyan doctrine using the most recent methodologies of modern linguistics, including a semiotic approach.
Keywords: predicate; predicative; predicator; principal member; subject; sign; signified; signifier